Stereoselective preparations of epoxy-, fluoro- and related derivatives of ricinoleic acid and 13(S)-hydroxyoctadeca-9(Z),11(E)-dienoic acid - Omar, Muhammad Nor; Hamilton, Richard J; Moynihan, Humphrey A (ARKAT USA Inc, 2003)
Methyl ricinoleate 4 and methyl 13(S)-hydroxyoctadeca-9(Z),11(E)-dienoate 7 were subjected to epoxidation using mCPBA, or tert-butyl hydroperoxide in the presence of vanadyl acetylacetonate or titanium (IV) isopropoxide with D-(-)- or L-(+)-diisopropyl tartrate. Epoxidations using mCPBA gave equal quantities of the disatereoisomeric epoxides 5/6 and 8/9 from 4 and 7 respectively. Other methods gave preferentially epoxides 5 or 8, except for treatment of 7 with tert-butyl hydroperoxide in the presence of titanium (IV) isopropoxide and L-(+)-diisopropyl tartrate which gave preferentially epoxide 9. Hydroxy-derivative 4, 7, 5, 6, 8 and 9 were converted into the fluoro-derivatives 16 - 21 by trimethylsilylation and treament with diethylaminosulphur trifluoride. Epoxides 6 and 9 were converted into 2-oxazolines 22 and 23 respectively by reaction with acetamide.